The religious knowledge, attitudes and practices of Chinese Catholic high schools students' in the Philippines - Yang, An-Jen (Animo Repository, 2002)
This study identifies the status and the factors affecting the religious education of 1802 students from 18 Chinese Catholic high schools in the Philippines. The survey was administered to all the 2000-2001 senior students. The dependent variables of this study were the students' religious knowledge, attitudes, and practices and 18 other independent variables (personal, parent and religion teacher factors) that affect them. The instruments used were the PASKO Questionnaires on religious knowledge and religious attitudes. A third questionnaire was an adaptation of a questionnaire on religious practices prepared and validated by Fr. Jose Calucag, SVD.Means were used to determine the status of the religious knowledge, attitudes, and practices of the students. Pearson Product-Moment Correlation was used to determine the coefficients of correlation between the three variables and between each of the said variables, and the static/non-static variables of the students, parents and religion teachers. Regression analysis was used to determine the multiple indices as best predictors for religious knowledge, attitudes, and practices. The study showed that the students have a good and clear understanding of different concepts on religious knowledge. The students' attitudes toward social involvement and the problems of doubts are however considered poor indicators.